Antecedents of memorable tourism experience related to behavioral intentions. Issue 12 (7th November 2017) - Coudounaris, Dafnis N.; Sthapit, Erose
Abstract: This study investigates the antecedent factors of memorable tourism experience (MTE) and their relationship to visitors' behavioral intentions (BIs); Kim, Ritchie, & McCormick, 2012 ). Based on a survey of 314 structured interviews among visitors to the zoo and museum in Rovaniemi, Finland, the study reveals different MTE dimensions than in Kim et al.'s study. Only four factors—hedonism, local culture, involvement, and knowledge—influence visitors' BIs. The results suggest the need to rebuild the scale of MTE by incorporating other relevant dimensions.